Effectiveness of Problem Based Learning Model Based on Comic in Increase the Ability to Think Creativity in Elementary School Students - A'yun, Qurrotal; Wardani, Imas Srinana (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Study This is based on the ability reason creative low students​ to understand the Topic of chain food. Research objectives: Is there any use in knowing the effectiveness of the PBL-based model comic in raising the ability to think creative in Elementary School Students? Research uses a quantitative approach through a quasi-experimental design type nonequivalent pretest-posttest control class design and technique taking sample in a technique of purposive sampling. The research sample consists of the origin student class VA consists of 29 children, as well as the student class VB consists of 31 children. Data collection using instrument test ability think creative. Based on what, an independent sample t-test was conducted, it was obtained mark significance of 0.000 was obtained, which shows that there is an increased ability to think creative, which is substantial in the group experiment if compared to with group control. Implications results study. This shows that the PBL model is based on comics, not only effective in increasing creative students' ability to think, but can also become an alternative innovative approach in science learning at the Basic level. Using comics as a learning medium makes it easier to understand complex concepts like chain food while simultaneously creating a fun and interactive learning atmosphere. Conclusion​ study This is a PBL model based on comics, effective in raising the ability reason creative students who include fluency, flexibility, originality, and detailed explanation in Elementary School.